Um estudo da aplicação do padrão AUTOSAR para desenvolvimento de funções em sistemas embarcados automotivos - Neme, João Henrique Zander (2017)
The automotive industry needs constant increase of quality and innovation to differentiate from competitors, but without impacting production costs. In the traditional development increasing complexity of a system directly increases the cost of production. To reverse this relationship it is necessary to implement modern development techniques and standards. This work intends to present some modern development techniques demonstrating the workflow necessary for the creation of modern automotive functions, providing a bibliography that demonstrates concepts and practices of the tool chain for this purpose. Initially, an overview of the development of automotive software and a comparison between the traditional methodology and the X-in-the-Loop approach is presented. Following the AUTOSAR standard is presented to be applied after the design of an automotive dashboard function.